Early life exposure to ambient particulate matter and Kawasaki disease: a systematic review and meta-analysis - Moncur, Christina; Kamotho, Mona; Jain, Tanisha; Weslock, Noah; Ragheb, Mark; Mitchell, Kerry (Frontiers in Cardiovascular Medicine, 2025)
IntroductionThough numerous air pollutants have been mechanistically associated with inflammation and vascular morbidity, particulate matter (PM) is one of the pollutants with the strongest association. However, PM is generally categorized according to aerodynamic diameters between 2.5 and 10 μg m−3 (PM10) and less than 2.5 μg m−3 (PM2.5). Given their differential ability to enter the bloodstream, these sizes play a crucial role in the local or systemic inflammatory responses elicited after exposure. Given that vascular inflammation is a key marker of Kawasaki Disease (KD), this systematic review aims to summarize the available data on the association between KD and perinatal and early childhood PM exposure and identify any pathophysiological links.MethodsA systematic search was conducted using PubMed and EMBASE. Studies with PM included as a predictor, and Kawasaki disease as an outcome were included. This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The risk of bias in the selected studies was assessed using the QUADAS-2 tool.ResultsEleven studies met the criteria for inclusion. All studies suggested an association between exposure to PM and increase risk or exacerbation of KD, though not all results reached statistical significance. Due to significant heterogeneity, pooled analyses were possible only in select studies for pre- and postnatal PM10 exposure and postnatal PM2.5 exposure. All studies identified immune-mediated inflammatory responses as a key pathophysiological link between exposure and KD, with PM10 noted as a significant risk factor for respiratory inflammation and poor maternal and child health, and PM2.5 for a wide range of adverse outcomes, especially in children and populations with preexisting inflammatory diseases. The role social, behavioral and environmental modifiers play in disease incidence was also highlighted.ConclusionParticulate matter exposure is associated with an increased risk of developing and exacerbating KD, especially in populations experiencing temporary increased sensitivity and in populations with preexisting inflammatory diseases.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023468937, PROSPERO CRD42023468937.